Developing Sundanese Language and Cultural Literacy in Early Learners through Educational Picture Board Games - Wulan Tini; Lenny Nuraeni; Sri Nurhayati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
The study explores the integration of storytelling using Educational Pictured Game Board as an innovative pedagogical approach to preserve the Sundanese language and cultural identity among early childhood learners at PAUD Sahabat Syurga. This method employed a qualitative design with data collected through interviews, observations, and documentation, focusing on children aged 5-6 years. The use of culturally resonant stories, traditional songs, and interactive educational tools made from recycled materials created an engaging and immersive learning experience. The results indicate significant improvements in children’s Sundanese vocabulary acquisition, narrative skills, and cultural awareness. Parental involvement played a crucial role in reinforcing language use at home, while teachers’ creativity and adaptability were key to delivering effective lessons. Challenges included limited parental fluency, resource constraints, and the dominance of Indonesian as the primary language in families. The study highlights the scalability of this approach to other regional languages and its potential to contribute to cultural preservation efforts. By demonstrating the effectiveness of culturally integrated storytelling, this research underscores the importance of early interventions in sustaining linguistic and cultural diversity. Future research should explore the longitudinal impacts of such initiatives and investigate the use of digital tools to modernize regional language education.